أثر جودة الخدمات المصرفية الإلكترونية على رضا العملاء في البنوك الإسلامية السعودية: Impact of the quality of electronic banking services on customer satisfaction in Saudi Islamic banks - فهد مطر المطيري (Journal of North African Economies, 2025)
This study aimed to measure the impact of the quality of electronic banking services in their dimensions (ease of use, saving time, confidentiality, safety) on customer satisfaction in Saudi Islamic banks, and to achieve the objectives of this study, the descriptive analytical approach was used, through resolution as a key tool for collecting data, and then addressing it using the program statistical packages for science and social sciences (spss), the results of the statistical analysis showed, that the quality of electronic banking services in Saudi Islamic banks in general was high, and that there is a significant impact Statistics on the quality of electronic banking services (ease of use, time saving, confidentiality, safety) on customer satisfaction in Saudi Islamic banks, and there is a statistically significant impact on the dimensions of the quality of electronic banking services (ease of use, time saving, confidentiality, safety) as well as customer satisfaction in Saudi Islamic banks. The study recommended that Saudi Islamic banks maintain the high level of the quality of electronic banking services and monitor them periodically, and that further studies on the quality of electronic banking services should be carried out by introducing other dimensions that were not mentioned in this study.